Human Genetic Variation in F3 and Its Impact on Tissue Factor–Dependent Disease - Park, Jin K.; Brake, Marisa A.; Schulman, Sol (Seminars in Thrombosis and Hemostasis, 2023)
Tissue factor (TF) is the primary initiator of blood coagulation in humans. As improper intravascular TF expression and procoagulant activity underlie numerous thrombotic disorders, there has been longstanding interest in the contribution of heritable genetic variation in F3, the gene encoding TF, to human disease. This review seeks to comprehensively and critically synthesize small case–control studies focused on candidate single nucleotide polymorphisms (SNPs), as well as modern genome-wide association studies (GWAS) seeking to discover novel associations between variants and clinical phenotypes. Where possible, correlative laboratory studies, expression quantitative trait loci, and protein quantitative trait loci are evaluated to glean potential mechanistic insights. Most disease associations implicated in historical case–control studies have proven difficult to replicate in large GWAS. Nevertheless, SNPs linked to F3, such as rs2022030, are associated with increased F3 mRNA expression, monocyte TF expression after endotoxin exposure, and circulating levels of the prothrombotic biomarker D-dimer, consistent with the central role of TF in the initiation of blood coagulation.
Keywords: tissue factor; F3; blood coagulation; thrombosis; genetics; GWAS